A Feasibility Study of Squash Croquettes at Jordan Plains, Novaliches, Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researcher choose squash croquette as the main product of the business a croquette is a small bread crumbed fried food that is usually made up of flour, egg, bread crumbs, milk, salt, and pepper.it is mixed with different ingredients to make different version of it and those are usually potato croquette, pork, chicken, beef, and other variety. But on this study the researcher choose squash as the main ingredients it will be sold on a stall that will be located at Jordan plains, Quezon city. They chose to have this product because its main ingredients squash has a lot of vitamins a nutrients that helps to have a good skin, clear vision and protection from lung cancer and mouth cancer.The method used on this feasibility study is survey method where in the researcher gave out questionnaire to be answered by the chosen respondents. This questionnaire contains essential question that is needed to gain information for the completion of the study. The researchers chose to this kind of method because through this, there is bigger chance to have a better and more accurate result. They can elaborate the questions more to have a cleared answers. After the study,it shows that the business with the main product of squash croquette if feasible. It underwent a survey and based on the answers of the chosen respondents, the product is acceptable on the market and business industry. 100% of the respondents agreed that it will be popular and acceptable in the market, so based on that 100% of agreement about its popularity, the business will be feasible and acceptable the moment it came out on the industry. Al lot of people and possible consumer will try the product and will eventually a usual customers. The business will be successful on the industry as it existence become longer on the industry. On this study, researchers focus and studied about the feasibility of squash croquette. They seek to find the number of acceptance of the product. The product is like a usual croquette but the main ingredients used is squash. They also offer other version of squash croquette such as pork, chicken, and beef. To know it is feasible, they used survey method wherein they gave questionnaires to the chosen respondents. After conducting the survey and computation of data gathered, the study shows that the study of squash croquette is feasible on the possible customers. 100% of the chosen respondents agreed that
Keywords: squash croquettes, feasibility study, BCP